Explorando Dados Urbanos: um estudo usando viagens de Tá xi da cidade de S ão Francisco - Martins, Karen S.; Cunha, Felipe D. (Anais do Workshop de Computação Urbana (CoUrb), 2018)
Vehicle networks have become a frequently studied topic of the Internet of Things. It allows communication between vehicles and access points along the streets, making the route safer for people. From studies of this network, it is possible to better understand people's behavior in big cities, including their routines, most frequented places for each weekday and mobility models. With the results, it can be created several applications for human benefit and improve network communication protocols. In this work, we analyze taxicabs' traces regarding encounters throughout the day in the city of San Francisco, USA. The goal is to show that there are standards in the number of times these vehicles meet, mainly by comparing weekends with weekdays. For the development, it was used temporal graphs, calibrated traces of the city's táxis and three metrics that are related to the number of encounters. The metrics explored were: repeated encounters throughout the day, repeated encounters throughout the day in the same place, and the ratio of the number of repeated encounters over the total number of encounters for each vehicle. As a result, we find some patterns in the vehicle routines.